Systematic Literature Review: Studies on Cost Stickiness Behavior under Uncertainty Condition - Fajar Meiyanti (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2024)
The uncertainty Based on previous research, cost behavior tends to be sticky when activity increases or decreasesThe purpose of this study is to determine the association of uncertainty with cost stickiness behavior through a systematic literature review. Using existing studies in the Scopus and Google Scholar databases, and future research. The analysis was conducted on 27 eligible articles based on the criteria and then mapped based on the year of research, author, research sample, observation period, theory used, variable measurement, research results, and research gap. Researchers found that the impact of uncertainty on cost stickiness still varies. Future research can discuss and expand the analysis to understand long-term uncertainties, such as global trade policy or climate change, as well as use a variety of measurements or expand the scope of research.